Dinâmica populacional e produção secundária de Excirolana braziliensis (Richardson, 1912) (ISOPODA, CIROLANIDAE) em uma praia exposta refletiva no litoral do sudeste do Brasil - RODRIGUES, Stefany Mattos Oliveira (2019)
This study evaluated the population dynamics and secondary production of cirolanid isopod, Excirolana braziliensis, on the exposed sandy beach North Red, Ubatuba, São Paulo coast. This study aimed to evaluate the variation in production of this isopod depending on the morphodynamic state of the beaches, using the data obtained in the Red North and available in the literature to examine relationships between abiotic variables, secondary production and P/B of E. braziliensis Sampling was performed monthly in Northern Red between May 2012 and June 2013 along five transects established perpendicular to the waterline in the intertidal zone. Sampling units were obtained every 3 meters along each transection using a cylindrical delimiter 30 cm in diameter. In the laboratory, subjects were measured and divided into size classes, and ash-free dry weight (AFDW) was calculated by subtracting ash mass (AM) for dry matter (DM). The high density of E. brasiliensis in reflective beach Red North (107 ind.m-2), was close to average density estimated to subtropical beaches (88 ind.m-2). Based on the literature raised were observed low density values toward beaches with thick grain, implying that this species seems to respond as the intertidal. A possible cause of the high density of E. brasiliensis in North Red Beach is the absence of congeneric Excirolana armata species on this beach. On the beaches of temperate region, Barra do Chuy and Arachania, observed higher values of asymptotic length compared to the Northern Red Beach; in the other words, subtropical beaches showed higher growth and lower asymptotic length compared to temperate beaches, and the last one shows lower mortality rates and longer life expectancy. Greater significant results were observed in mortality beaches with coarse grain size and small extent, agreeing with the Severity Hypothesis Environment. The production shows higher values in fine sand beaches and gentler slopes, indicating that this isopod reaches higher production at intermediate / dissipative conditions. In addition, low values in the density of recruits resulted in lower renewal fee on the beach studied.